Idealer og realiteter i moderne psykisk helsearbeid - Karlsen, Rune (Nordisk Tidsskrift for Helseforskning, 2012)
Ideals and realities in modern mental healthcareThe ideals of mental health care differ from the psychiatry of earlier times. This difference is characterized by dissociation from a previous authoritarian and staff-administered practice in the psychiatric institutions. Client participation and interdisciplinary work, equality and relation building, resource orientation and mastery are the new professional ideals.Critical reading of patient records suggests a lack of agreement between professional ideals and practical realities in current Norwegian decentralized mental health work. The staff is still clinging to the old authority structures from the psychiatric hospitals, and they do not manage to show that they have their own profession. The users are too passive in their own treatment program. The staff lacks written language for describing the establishment and maintenance of personal relations. The new professional groups adopt the old ways of proceeding, and do not add new professional approaches. The article places a critical focus on the inherent conservatism of tacit knowledge.